Analisis Diagnosa Rujukan Peserta BPJS Kesehatan Terhadap 144 Diagnosa di Fasilitas Kesehatan Tingkat Pertama Klinik Sat Brimob Polda Riau - Josua Tobing, Nur Maimun, (Jurnal Martenity and Neonatal, 2016)
Competency standard doctor indonesia on 2012 , 736 list of disease there are 144 disease that must be controlled full by the graduates and hoped it doctor primary services can actually diagnose and do penatalaksanaan independently and be completed. Standard referral patients bpjs at the health facilities tingat first clinic one brimbob polda riau of the number of a visit that can be referred as many as 7.5 % of numerical quantities a visit that should each patient insurmountable at the clinic one brimob, but because example facilities, facilities and human resources that is at the clinic one brimob, many participants bpjs who be completed but referred to health facilities a higher level or also called the hospital . This research to know the diagnosis referral bpjs participants health against 144 the diagnosis at the clinic who does a thing premat brimob polda riau the year 2015 .Research methodology is descriptive with a qualitative approach. The subject of study 4 informants by the formation of one heads a clinic, one general practitioner , 1 people nurses and midwives 1 people .The withdrawal of the data by using in-depth interviews with analysis of the content analysis. The results of the study found that human resources the figures are still inadequate because the workloads many, physical environment does not support because of a lack of room that is, of existing infrastructure are still not complete the number, and medicines that is not complete in overcome 144 the diagnosis be completed of ministry the basic health.Should the increase in the number of human resources, expected development clinic one brimob that room that is could be many more.Expected facilities and infrastructure more furnished, and a long replaced by more worthy used.Expected drugs more furnished the number, especially must be in accordance with the diagnosis be completed in basic service.